Pb‐Reduced CsPb0.9Zn0.1I2Br Thin Films for Efficient Perovskite Solar Cells. Issue 25 (16th May 2019) - Sun, Hongrui; Zhang, Jing; Gan, Xinlei; Yu, Luting; Yuan, Haobo; Shang, Minghui; Lu, Chaojie; Hou, Dagang; Hu, Ziyang; Zhu, Yuejin; Han, Liyuan
Abstract: Fabrication of efficient Pb reduced inorganic CsPbI2 Br perovskite solar cells (PSC) are an important part of environment‐friendly perovskite technology. In this work, 10% Pb reduction in CsPb0.9 Zn0.1 I2 Br promotes the efficiency of PSCs to 13.6% (AM1.5, 1sun), much higher than the 11.8% of the pure CsPbI2 Br solar cell. Zn 2+ has stronger interaction with the anions to manipulate crystal growth, resulting in size‐enlarged crystallite with enhanced growth orientation. Moreover, the grain boundaries (GBs) are passivated by the Cs‐Zn‐I/Br compound. The high quality CsPb0.9 Zn0.1 I2 Br greatly diminishes the GB trap states and facilitates the charge transport. Furthermore, the Zn4s‐I5p states slightly reduce the energy bandgap, accounting for the wider solar spectrum absorption. Both the crystalline morphology and energy state change benefit the device performance. This work highlights a nontoxic and stable Pb reduction method to achieve efficient inorganic PSCs. Abstract : 10% Pb reduction in CsPb0.9 Zn0.1 I2 Br boosts the efficiency of the solar cell device. Zn 2+ results in high quality crystalline and energy state modulation, greatly reducing the trap states and promoting the charge transport in the device. This work highlights that Zn is an effective and stable Pb reducer that compares well to the chemical unstable Sn, in efficient CsPbX3 based PSCs.